Photoinduced curcumin derivative-coatings with antibacterial properties1. Issue 104 (11th November 2015) - Condat, M.; Mazeran, P.-E.; Malval, J.-P.; Lalevée, J.; Morlet-Savary, F.; Renard, E.; Langlois, V.; Abbad Andalloussi, S.; Versace, D.-L.
<x xml:space="preserve">Abstract</x> Synthesis of antibacterial coatings derived from epoxidized soybean oil and curcumin for the efficient inhibition of bacteria proliferation.